2021
DOI: 10.3390/ijms22116158
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Key Ion Channels and Transport Proteins in Age-Related Hearing Loss

Abstract: The auditory system is a fascinating sensory organ that overall, converts sound signals to electrical signals of the nervous system. Initially, sound energy is converted to mechanical energy via amplification processes in the middle ear, followed by transduction of mechanical movements of the oval window into electrochemical signals in the cochlear hair cells, and finally, neural signals travel to the central auditory system, via the auditory division of the 8th cranial nerve. The majority of people above 60 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 249 publications
(308 reference statements)
0
25
0
Order By: Relevance
“…For instance, Schulte and Schmiedt [60] found that EP levels decrease first in the apex of the cochlea before decreasing in other regions of the cochlea as aging occurs, which is correlated with the expression levels of Na,K-ATPase found in the stria. Na,K-ATPase is important for ion transport, and there is a decrease in its presence with age in the stria [63], where its expression was found to be reduced up to 80% in aged CBA/CaJ mice [48,53]. Moreover, localization of decreasing Na,K-ATPase expression was seen to occur in the same regions where EP levels dropped [63].…”
Section: Cochlear Agingmentioning
confidence: 92%
See 4 more Smart Citations
“…For instance, Schulte and Schmiedt [60] found that EP levels decrease first in the apex of the cochlea before decreasing in other regions of the cochlea as aging occurs, which is correlated with the expression levels of Na,K-ATPase found in the stria. Na,K-ATPase is important for ion transport, and there is a decrease in its presence with age in the stria [63], where its expression was found to be reduced up to 80% in aged CBA/CaJ mice [48,53]. Moreover, localization of decreasing Na,K-ATPase expression was seen to occur in the same regions where EP levels dropped [63].…”
Section: Cochlear Agingmentioning
confidence: 92%
“…More specifically, ion channel dysfunction in the auditory system has been shown to negatively impact hearing by mainly impacting the K + channels that affect the generation of the EP needed for hair cell depolarization. Here, age-related hearing disorders are often linked to a decrease in EP and reduction in K + channel functionality; reductions which while yet unconfirmed, can reasonably be attributed to inflammation and mitochondrial dysfunction [48].…”
Section: Necroptosis Mitochondrial Dysfunction and Inflammaging In The Inner Earmentioning
confidence: 97%
See 3 more Smart Citations